ANALISIS PENERAPAN PSAP NO. 07 PADA AKUNTANSI ASET TETAP DI KANTOR KECAMATAN CIWIDEY. - Rosidah, Idah; Kesumah, Priatna; Kurniawan, Sandy; Gunardi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2024)
This research aims to analyze the application of Government Accounting Standards Statement (PSAP) No. 07 related to fixed asset management at the Ciwidey District Office. The problem studied is the implementation of PSAP No. 07 which has not been optimal in the aspects of recording, measuring, depreciation and disclosure of fixed assets, as well as the technical obstacles faced. This research uses a descriptive method with a qualitative approach, where data is obtained through documentation of financial reports, interviews with the head of the accounting department, and direct observation of the accounting information system used. The research results show that the Ciwidey District Office has implemented most of the provisions of PSAP No. 07, but there are still obstacles in integrating accounting information systems with standard fixed asset reporting. In conclusion, the implementation of PSAP No. 07 on fixed assets needs to be improved through information system optimization and external audits to ensure transparency and reporting accuracy. The advice given is to strengthen the integration of the accounting system and carry out routine audits to comply with applicable accounting standards.